1985
DOI: 10.1111/j.1600-079x.1985.tb00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Superior Cervical Ganglionectomy on Dimethylbenz(a)anthracene‐Induced Mammary Tumors in the Rat

Abstract: The role of the pineal in regulating the oncogenic processes was explored in Sprague-Dawley female rats by comparing incidence and growth of mammary tumors in animals subjected to superior cervical ganglionectomy (SCGx) or blinding and anosmia (BAs) with that of intact rats treated with 7-12-dimethylbenz(a)anthracene (DMBA). The surgery was performed at the age of 56 days, 1 day following the administration of the carcinogen. Growth of mammary tumors was studied, and 15 weeks later the rats were sacrificed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Changes in mean volume of AT tumor in intact untreated rats or rats 1984; Chang et al, 1985;Kothari et al, 1982Kothari et al, , 1984Shah et al, 1984;Tamarkin et al, 19811. In these studies, MEL was found to suppress tumor formation, and in some circumstances, pinealectomy was found to enhance it. Chang et al [1985] also found that superior cervical ganglionectomy (a procedure which usually mimics pinealectomy) also inhibited carcinogenesis in this model. In addition, women with estrogen receptor (ER)-positive breast cancer have been found to have an altered pattern of MEL secretion which was not seen in women with ER-negative disease [Tamarkin et al, 19821.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in mean volume of AT tumor in intact untreated rats or rats 1984; Chang et al, 1985;Kothari et al, 1982Kothari et al, , 1984Shah et al, 1984;Tamarkin et al, 19811. In these studies, MEL was found to suppress tumor formation, and in some circumstances, pinealectomy was found to enhance it. Chang et al [1985] also found that superior cervical ganglionectomy (a procedure which usually mimics pinealectomy) also inhibited carcinogenesis in this model. In addition, women with estrogen receptor (ER)-positive breast cancer have been found to have an altered pattern of MEL secretion which was not seen in women with ER-negative disease [Tamarkin et al, 19821.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies the 7,12 DMBA (7,12, dimethylbenz[a]anthracene)-induced rat mammary adenocarcinoma model (a hormone responsive model) was employed. By using procedures such as blinding or removal of the olfactory bulbs that provided a maximum stimulation of melatonin secretion, the volume of DMBA-induced mammary tumors decreased significantly [102,103]. It is important to note that these procedures also reduce the circulating levels of estradiol and prolactin [103] which may also contribute to the decrease of tumor volume.…”
Section: Melatonin Effects In Experimental Models Of Breast Cancermentioning
confidence: 99%
“…By using procedures such as blinding or removal of the olfactory bulbs that provided a maximum stimulation of melatonin secretion, the volume of DMBA-induced mammary tumors decreased significantly [102,103]. It is important to note that these procedures also reduce the circulating levels of estradiol and prolactin [103] which may also contribute to the decrease of tumor volume. Chronic late afternoon injections of melatonin (250 lg/mg/day) suppressed the development and growth of N-methyl-N-nitrosourea (NMU)-induced and transplanted R3230 AC rat mammary tumors [104].…”
Section: Melatonin Effects In Experimental Models Of Breast Cancermentioning
confidence: 99%